STUDENTS’ PERCEPTION TOWARD TEACHERS’ FEEDBACK IN WRITING CLASS AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Tabah Maulinda Sari (PBI 15 UMY 071, 2015)
*71 Teachers’ feedback gives powerful influences on learning and achievement, especially in students’ writing skill. This research is aimed to know the students’ perception toward types of teachers’ feedback in writing class at English Education Department, Universitas Muhammadiyah Yogyakarta. On the other hand, this research also wants to find out the effect of teachers’ feedback toward students’ writing. This research used qualitative design. In this kind of qualitative research design, the researcher chose interview as the instrument to collect the data. There were six participants as the respondents in this study. They were the students of English Education Department from batch 2014. Participants were chosen based on some criteria. They were students who got high, middle and low score in writing class. The purpose is to get different information from different level. In analyzing the data, the researcher used three kinds of coding including open coding, axial coding and also selective coding to get the final categorization of the data. Before analyzing the data, the researcher had already done member checking to get the data trust worthy. The result of the research showed that there were two ways that the teachers gave feedback to the students, the first is written feedback and the second is oral feedback. There were also positive and negative feedbacks in writing class. Teachers’ feedback gave so many benefits to the students’ writing in improving their writing TEACHERS’ FEEDBACK IN WRITING CLASS vi skill. Teachers’ feedbacks also helped the students in grammar and in new vocabulary.